Satisfaction with the institution as a predictor of the intention todrop out in online higher education (2024)
Enrollment in online higher education (OHE) programs has witnessed a substantialincrease, owing to the benefits and added value it offers students. However, one ofthe main challenges in this educational modality is attrition. While research on attri-tion in online settings is plentiful, studies on student satisfaction with higher educa-tion institutions (HEIs) in these settings are still nascent. Therefore, this article aimedto assess the impact of student satisfaction with HEIs on their intention to drop out inthe OHE environment, seeking to identify specific constructs that influence studentsatisfaction in this educational modality. To achieve this, a partial least squares struc-tural equation modeling was employed to examine the relationship between satisfac-tion with the institution and the intention to drop out. The model was parameterizedusing data from a sample of 524 participants across the 32 departments of Colombia.The study revealed that satisfaction with various aspects of OHE variably affects over-all satisfaction with the HEI and the intention to drop out. Despite significant effectsizes, the lack of statistical significance in certain areas suggests further research.These findings are crucial for developing strategies to improve the educational experi-ence and reduce attrition in OHE.